A Generalized Kinetic Framework Applied to Whole‐Cell Bioelectrocatalysis in Bioflow Reactors Clarifies Performance Enhancements for Geobacter Sulfurreducens Biofilms. Issue 10 (16th May 2019) - Zarabadi, Mir Pouyan; Couture, Manon; Charette, Steve J.; Greener, Jesse
Abstract: A common kinetic framework for studies of whole‐cell catalysis is vital for understanding and optimizing bioflow reactors. In this work, we demonstrate the applicability of a flow‐adapted version of Michaelis‐Menten kinetics to an electrocatalytic bacterial biofilm. A three‐electrode microfluidic biofilm flow reactor measured increased turnover rates by as much as 50 % from a Geobacter sulfurreducens biofilm as flow rate was varied. Based on parameters from the applied kinetic framework, flow‐induced increases to turnover rate, catalytic efficiency and device reaction capacity could be linked to an increase in catalytic biomass. This study demonstrates that a standardized kinetic framework is critical for quantitative measurements of new living catalytic systems in flow reactors and for benchmarking against well‐studied catalytic systems such as enzymes. Abstract : Go with the flow : Cell‐based biotransformations are well‐known for food and beverage production, but only recently has the domain of "whole‐cell biocatalysis" become a recognized area of research. Here, a flow‐adapted version of Michaelis–Menten kinetics is used to study whole‐cell catalysis in flow. This proof‐of‐principle monitors the bioelectrocatalysis of a Geobacter sulfurreducens biofilm by using a three‐electrode microfluidic flow reactor. Measured turnover rates are interpreted based on standard parameters such as K M and ϵ, and point to an increase in accessible electrocatalytic bacteria with flow.